Determinação de condições operacionais adequadas na desidratação do minério de gipsita para obtenção de um gesso beta reciclável - Cavalcanti, Leonardo Barbosa (2006)
Operational conditions of temperature and pressure had been determined under which the thermal dehydration of the gypsum ore occurs producing a type of recyclable beta plaster. With the resolution of the CONAMA nº 307, of July 5th of 2002, the plaster waste proceeding from the civil building became one waste of difficult discarding, a time that this material is considered such as contaminante for the excessively component ones of a rubbish and considers that technology for its recycling still was not developed. In this work it was elaborated and confectioned a batch reactor in laboratory scale for beta plaster production from the ore gypsum and under pressure above of the atmospheric pressure. This excess of pressure was gotten holding back part of the water vapor produced with the dehydration of the ore, by means of a valve of the automatic relief type. The dehydration of the gypsum ore in these conditions gives origin to a beta plaster with superior mechanical characteristics to the plaster conventionally produced by the majority of the existing productive processes in the Polar Region Plasterer of the Araripe - Pernambuco. Under controlled pressure of 0.65 atm above of the atmospheric pressure and approximately 150 ºC, the plaster does not present breaked crystals, provoked for the abrupt exit of the dehydration water of the calcium sulphate di-hydrate. Some important properties of the beta plaster, produced under pressure had been tested and compared with plaster produced under conventional conditions of manufacture. The tests had verified values of the dehydration water, to confirm the final conversion of the dehydration reaction, and properties as unitary mass, flexion rupture modulus, hardness and setting time. The beta plasters produced under pressure had been tested in two life cycles and in both they had presented characteristics of a plaster with well formed crystals, homogeneously distributed and of low inter- and intra-crystals porosities. Its comparison with conventional plasters had shown superiority how much to the mechanical properties, mainly in relation to both in its second life cycles. The recycling index was of 100 %. So is given credit that the industrial productive processes practiced in the Polar Region Plasterer need technique adaptations, if it desires to the recycling of part of plasters originated in building and demolition, such as waste of the plates, blocks, plaster walls, and so on, and the wastes also originated in the proper processes of manufacture of these plaster premoldeds